Doxycycline Inhibits Cancer Stem Cell-Like Properties via PAR1/FAK/PI3K/AKT Pathway in Pancreatic Cancer - Liu, Huijuan; Tao, Honglian; Wang, Hongqi; Yang, Yuyan; Yang, Ru; Dai, Xintong; Ding, Xiujuan; Wu, Haidong; Chen, Shuang; Sun, Tao (Frontiers in Oncology, 2021)
Pancreatic cancer stem cells (CSCs) play an important role in the promotion of invasion and metastasis of pancreatic cancer. Protease activation receptor 1 (PAR1) is closely related to malignant progression of tumors, however, its effects on pancreatic cancer stem cell-like (CSC-like) properties formation have not been reported. In this work, the effects of PAR1 on pancreatic cancer stem cell-like (CSC-like) properties formation were studied. PAR1 overexpression can induce CSC-like properties in Aspc-1 cells, whereas interference of PAR1 in Panc-1 cells showed the contrary results. Data on patients with pancreatic cancer obtained from TCGA showed that high PAR1 expression and focal adhesion kinase (FAK) protein considerably affect the prognosis of patients. Further experiments showed that PAR1 could regulate FAK, PI3K, and AKT phosphorylation and the epithelial–mesenchymal transformation (EMT) in Aspc-1 and Panc-1 cells. Doxycycline, as a PAR1 inhibitor, could effectively inhibit the CSC-like properties of pancreatic cancer cells and the FAK/PI3K/AKT pathway activation. Doxycycline inhibits the growth of pancreatic cancer and enhances the treatment effect of 5-fluorouracil (5-FU) in Panc-1 xenograft mouse model. In conclusion, PAR1 promotes the CSC-like properties and EMT of pancreatic cancer cells via the FAK/PI3K/AKT pathway. Doxycycline inhibits the pancreatic cancer through the PAR-1/FAK/PI3K/AKT pathway and enhances the therapeutic effect of 5-FU.